Fostering Diversity and Moderation Through Multicultural Education: Insights from Pesantren Ulul Albab Yogyakarta - Maunah, Binti; Afnan Habibi, Muhammad; Zakiya Pratiwi , Etty (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This article looks at multicultural education at Ulul Albab Balirejo Umbulharjo Student Boarding School, Yogyakarta. Multicultural education is about understanding and accepting differences in religion, culture, gender, social class, race, ability and age. Multicultural education is the best way to deal with diversity in Islamic boarding schools. Multicultural education helps students deal with globalisation by teaching them about different cultures. Successful multicultural education produces students with high tolerance. With multicultural education, students will understand and appreciate diversity. Multicultural education in boarding schools helps students learn from each other and teaches them to be moderate and to respect other cultures. The research method is qualitative and descriptive. The data was collected through interviews, observation and documents. This study shows that multicultural education training is about not discriminating based on ethnicity, class and gender. Pondok Pesantren Ulul Albab Balirejo Umbulharjo Yogyakarta also teaches Arabic and English. Pesantren Ulul Albab Balirejo Umbulharjo Yogyakarta is an example of Islam as a religion of peace. It promotes pluralism and multicultural education. It also works to reduce institutional egoism and promote diversity. To strengthen its role, it needs to reform its curriculum to integrate multicultural values into character education.